2020
DOI: 10.12997/jla.2020.9.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Select Macrophage Noncoding RNAs of Interest in Cardiovascular Disease

Abstract: Cardiovascular disease remains a leading cause of morbidity and mortality worldwide. Aspects of disease severity that are associated with heightened inflammation, such as during atherosclerosis or after myocardial infarction, are correlated with macrophage activation and macrophage polarization of the transcriptome and secretome. In this setting, non-coding RNAs (ncRNAs) may be as abundant as protein-coding genes and are increasingly recognized as significant modulators of macrophage gene expression and cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Several studies have shown that macrophages play distinct roles in different stages of carotid atherosclerosis. During the early stages of CAS, the regression of plaque is facilitated by the clearance of excessive macrophages through phagocytosis ( 13 ). In the late stage of CAS, due to local environmental damage and other reasons, excessive apoptosis of macrophages and obstacles in clearing cell debris can lead to the formation of necrotic cores in the plaque and a decline in plaque structural stability ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that macrophages play distinct roles in different stages of carotid atherosclerosis. During the early stages of CAS, the regression of plaque is facilitated by the clearance of excessive macrophages through phagocytosis ( 13 ). In the late stage of CAS, due to local environmental damage and other reasons, excessive apoptosis of macrophages and obstacles in clearing cell debris can lead to the formation of necrotic cores in the plaque and a decline in plaque structural stability ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dozens of lncRNAs have been reported to affect the development of atherosclerosis. Prior studies showed that specific lncRNAs regulate cells in arteries, including endothelial cells, vascular smooth muscle cells (VSMCs), and macrophages 4 , 6 , 7 . For instance, lncRNA H-19 is known to increase VSMC proliferation 8 , whereas lncRNA-p21 inhibits it 9 .…”
Section: Introductionmentioning
confidence: 99%